2019
DOI: 10.1177/1757975918811087
|View full text |Cite
|
Sign up to set email alerts
|

What are the roles of community health workers? Looking back at the philosophies of primary health care

Abstract: This commentary discusses the different roles of community health workers (CHWs), their challenges and limitations in a historical perspective of primary health care (PHC). We first try to show that the comprehensive philosophy of PHC promulgated in Alma-Ata proposed the role of CHWs as actors who work in community development. On the other hand, in the 1980s, with the emergence of the selective philosophy of PHC, CHWs’ role was more affiliated with the health system. We conclude our pitch about the balance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Research has shown that most engagement with the CHW workforce has been around upskilling to improve the health and empowerment in the communities they serve. 58 Much has been documented about CHWs as a liaison between the formal healthcare system 13 and the community and as a vital strategic resource to achieve global health goals, the actual CHWs and their own needs have been grossly overlooked. There is sufficient evidence to inform decision-makers about the factors that motivate CHWs into performing their roles effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that most engagement with the CHW workforce has been around upskilling to improve the health and empowerment in the communities they serve. 58 Much has been documented about CHWs as a liaison between the formal healthcare system 13 and the community and as a vital strategic resource to achieve global health goals, the actual CHWs and their own needs have been grossly overlooked. There is sufficient evidence to inform decision-makers about the factors that motivate CHWs into performing their roles effectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study of the professional role, it is fundamental to know where one starts from and what path one has followed. On an international level, although the origin of PHC is known [ 3 ], there is no evidence of work that has analysed the process by which a new role has been configured, which is essential to design future strategies, given that there is still, a need to clarify this role [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…CHWs' work is important to primary health care [11,12] and was essential in previous crises, such as H1N1 and Zika [2]. Some current papers have pointed out the potentially important work of CHWs in the face of the coronavirus pandemic [9,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%